The Role Of Sustainability Report In Increasing Firm Value - Ubaidillah, Moh.; Murwani, Juli; Novitasari, Maya (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
Firm value is important for companies because it can attract investors to invest. Increasing company value is not easy because management needs to do various ways, one of which is to do a sustainability report. The purpose of this study was to determine the effect of profitability and company size on firm value with sustainability report as a moderating variable. The sample of this study used 140 manufacturing companies in the food and beverage sub-sector with data collection techniques using purposive sampling. The analysis technique uses multiple linear regression with SPSS tools. The results of this study indicate that profitability and company size have a positive effect on firm value. Sustainability report is able to moderate the effect of profitability and company size on firm value.